Portal corporativo para gestão do conhecimento: alinhando pessoas, informação e estratégia organizacional em uma instituição de ensino superior privada - Weber, Claudiane (2010)
This research proposed to investigate how to develop and implant a corporate portal to assist in knowledge management in a Private Institution of Higher Education, based on people, information and organizational strategy. Considering the peculiarities of the context and academic knowledge, more specifically, it referred to a proposal to build a conceptual model of corporate portal for knowledge management in the academic context, based on organizational knowledge of a Private Institution of Higher Education. The research of this dissertation, of qualitative and quantitative nature, is characterized as a case study. The goals were achieved through a combination of two lines of action: the first related to the theoretical construction based on literature, and the second consists of a questionnaire applied to the technical-administrative employees of private institution of higher education (IESP). Based on the methods employed, it was possible to: a. collect the informational and knowledge needs of the IESP employees; b. verify how information and knowledge are treated in the institution in order to be linked to the organizational strategy; c. study the types of existing portals; and d. study the information and knowledge management in private institutions of higher education . From these results it was possible to delineate a conceptual model of portal for the management of knowledge in its tacit and explicit part in the academic context.